Comparative Evaluation of Traditional and Mechanical Maize Threshing Techniques in Major Maize Growing Districts of Karnataka - Tejas Kumar N; H.N. RameshBabu (The Bioscan, 2026)
This study was conducted to comparatively evaluate traditional and mechanical maize threshing techniques in major maize growing districts of Karnataka namely Chitradurga, Davanagere, Tumkur, Hassan, and Chikkamagaluru. The investigation aimed to assess threshing efficiency, operational cost, labour utilization, post-harvest losses, and economic feasibility of different maize threshing methods. A multistage sampling technique was employed for selecting districts, taluks, villages, and respondents. Primary data were collected from maize-growing farmers through structured interviews, while secondary data were obtained from agricultural reports and district records. The major traditional threshing methods identified were bare hand shelling, hand beating, stick beating, and bullock trampling, whereas engine-operated threshers, tractor- operated shellers, and power-operated threshing machines represented mechanical methods. Results revealed that mechanical threshing methods significantly reduced labour requirement, threshing duration, and post-harvest losses compared to traditional methods. Mechanical methods also provided higher threshing efficiency and economic returns despite higher initial investment and maintenance costs. Among the districts studied, Davanagere and Tumkur showed greater adoption of mechanized threshing systems due to larger operational holdings and labour scarcity. Farmers in Hassan and Chikkamagaluru faced challenges related to terrain and machine accessibility. The study concluded that mechanization in maize threshing improves operational efficiency, minimizes post-harvest losses, and enhances farmer profitability. Promotion of custom hiring centres, subsidy support, and training programmes can enhance adoption of mechanical threshing technologies among small and marginal farmers in Karnataka.